MANFAAT KAJIAN FILASAFAT, NILAI ETIKA DAN PRAGMATIS ILMU PENGETAHUAN UNTUK MELAKUKAN PENELITIAN ILMIAH - Winata, Tjen Dravinne (Jurnal Ilmiah Widya, 2014)
To conduct a scientific research, the students of the Academy/University in Indonesia need to know the scientific method, ethical values and the value of the examined from pragmatic philosophy of science.The purpose of this paper is to obtain an overview of the rules of the scientific method in conducting a scientific research, through the study of philosophy of science, ethics, values and pragmatic value in searching for the truth of science. The method used literature review with a qualitative retrospective approach. It can be concluded that: (1) the scientific method that is implemented in a responsible and legal research, regulations would ensure the validity of research results, (2) The fundamental thing in conducting scientific research is a systematic, correct, clear and logical scientific methods as well as appropriate defensible laws or rules of the study, (3) The scientific method as measures, laws or rules in seeking the truth of science are: (a) formulation of the problem, (b) the filing of a hypothesis, (c) the process of deduction hypothesis through the study of literature, (d) Proving the hypothesis through the process of induction, (e) the acceptance of the results of the research become a new scientific theory or science that is constructive.